Hashimoto's Encephalopathy and Seizure Disorders - Li, Jie; Li, Fengzhen (Frontiers in Neurology, 2019)
Hashimoto’s encephalopathy(HE) is a rare clinically heterogenous condition with increased antithyroid autoantibodies. It has been increasingly recognized over the last several years as an important treatable cause of autoimmune encephalopathy. Thyroid associated antibodies such as anti-TPO, thyroglobulin antibody, thyrotropin receptor antibody were found in HE patients with epilepsy. But electroencephalography and imaging findings is not specific to HE patients and can be seen in encephalopathies resulting from other causes. Although antithyroid antibodies is important when HE was diagnosed. Their role in the underlying disease pathogenesis remains uncertain. It is suggested that thyroid associated antibodies are rather hallmarks of HE than playing a direct role in the pathophysiology of HE. Approximately two thirds of patients of HE experience seizure disorders. Seizure disorders accompany with HE are usually refractory to antiepileptic drugs unless immunotherapy were used. Common anticonvulsant therapy alone is usually ineffective, Some patients did not respond to any antiepileptic drugs. The use of immunotherapy can effectively control seizure disorders. Awareness of HE has increased over the last several years but it is still relatively uncommon. However, if it is diagnosed and treated correctly, The prognosis of the disease is good. Therefore, it is important to know about the characteristic of HE.